Efficiency and productivity effects of bank mergers: Evidence from the Greek banking industry - Rezitis, Anthony N. (Economic modelling, 2008)
The main purpose of this study is to investigate the effect of acquisition activity on the efficiency and total factor productivity of Greek banks. A stochastic output distance function is used to construct a generalized output Malmquist productivity index based on the methodological framework of Orea [Orea, L., 2002. Parametric decomposition of a Generalized Malmquist Productivity Index. Journal of Productivity Analysis 18, 5–22]. The results of the present study indicate that the effects of mergers and acquisition on technical efficiency and total factor productivity growth of Greek banks are rather negative. In particular, the technical efficiency of merger banks decreased in the period after merging, while that of non-merger banks increased over the same period. Furthermore the decrease in total factor productivity for merger banks for the period after merging can be attributed to an increase in technical inefficiency and the disappearance of economies of scale, while technical change remained unchanged compared to the pre-merging level.